The Influence of the Picture and Picture Type Cooperative Learning Model on the Color Recognition Ability of 4-5 Year Old Children - Aprilia Wahyuning Fitri; Maulidah Fitria (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2021)
This study aims to determine the effect of the picture & picture-type cooperative learning model on children's ability to recognize colors. This research is experimental research with a pre-experimental design which was carried out based on the pre-test and post-test stages. The research subjects were 21 children aged 4-5 years at Pertiwi Kindergarten 14.02.01 Prembun, Kebumen. The data collection method in this research uses observation and documentation. The data analysis technique in this research uses paired samples T-Test with a significance level 0.05. Color recognition using cooperative picture & picture types influences the color recognition ability of children aged 4-5 years. The ability to recognize colors in the pre-test shows that the ability to recognize colors is still low. Next, the children are given treatment in the form of a picture & picture-type cooperative learning model for 3 days, then the children are given the colors in the same picture again as a post-test. The results of the paired samples T-Test were 0.000 < 0.05, which means there was a change in the ability to recognize colors before and after the treatment in the form of a picture & picture type cooperative learning model.